Intraperitoneal Instillation of Lidocaine Improves Postoperative Analgesia at Cesarean Delivery: A Randomized, Double-Blind, Placebo-controlled Trial. Issue 3 (September 2017) - Patel, R.; Carvalho, J.C.; Downey, K.; Kanczuk, M.; Bernstein, P.; Siddiqui, N.
Abstract : ( Anesth Analg . 2017;124(2):554–559) Poorly controlled postpartum pain can place a patient at risk for chronic pain, postpartum depression, and negatively impact maternal-fetal interactions. Although multimodal analgesia has greatly improved pain control in general for these women, there remain a proportion of patients who report inadequate postoperative pain relief. Intraperitoneal local anesthetics, which have proven successful in abdominal surgery pain control, may be an effective adjunct. The authors of this study evaluated the effect of intraperitoneal lidocaine on postcesarean delivery pain as part of a multimodal analgesia regimen.